2016
DOI: 10.1097/ncq.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Missed Nursing Care and Unit-Level Nurse Workload in the Acute and Post-Acute Settings

Abstract: This study replicates previous research on the nature and causes of missed nursing care and adds an explanatory variable: unit-level nurse workload (patient turnover percentage). The study was conducted in California, which legally mandates nurse staffing ratios. Findings demonstrated no significant relationship between patient turnover and missed nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 26 publications
4
41
1
2
Order By: Relevance
“…In all studies missed care was assessed by a survey completed by nurses or, for two studies, patients (Dabney & Kalisch, ; Weiss, Yakusheva, & Bobay, ). Eight studies (Cho, Kim, Yeon, You, & Lee, ; Dabney & Kalisch, ; Friese, Kalisch, & Lee, ; Kalisch, Tschannen, & Lee, ; Kalisch, Tschannen, Lee, & Friese, ; Kalisch et al., ; Orique et al., ; Palese et al., ) reported using a version of the MISSCARE survey (Kalisch & Williams, ); seven studies (Al‐Kandari & Thomas, ; Ausserhofer, et al., ; Ball, et al., ; Ball, et al., ; Bruyneel, et al., ; Griffiths, Dall'Ora, et al., ; Zander et al., ) used a survey developed for the Registered Nurse Forecasting (RN4Cast) study (Sermeus et al., ). One used the Basel Extent of Rationing Nursing Care Assessment (BERNCA) revised (Schubert et al., ), a version of the International Hospital Outcomes Survey (IHOS) (Al‐Kandari & Thomas, ) and one the Quality of Discharge Teaching Scale (QTDS) content delivered sub‐scale (Weiss et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all studies missed care was assessed by a survey completed by nurses or, for two studies, patients (Dabney & Kalisch, ; Weiss, Yakusheva, & Bobay, ). Eight studies (Cho, Kim, Yeon, You, & Lee, ; Dabney & Kalisch, ; Friese, Kalisch, & Lee, ; Kalisch, Tschannen, & Lee, ; Kalisch, Tschannen, Lee, & Friese, ; Kalisch et al., ; Orique et al., ; Palese et al., ) reported using a version of the MISSCARE survey (Kalisch & Williams, ); seven studies (Al‐Kandari & Thomas, ; Ausserhofer, et al., ; Ball, et al., ; Ball, et al., ; Bruyneel, et al., ; Griffiths, Dall'Ora, et al., ; Zander et al., ) used a survey developed for the Registered Nurse Forecasting (RN4Cast) study (Sermeus et al., ). One used the Basel Extent of Rationing Nursing Care Assessment (BERNCA) revised (Schubert et al., ), a version of the International Hospital Outcomes Survey (IHOS) (Al‐Kandari & Thomas, ) and one the Quality of Discharge Teaching Scale (QTDS) content delivered sub‐scale (Weiss et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies missed care was assessed by a survey completed by nurses or, for two studies, patients (Dabney & Kalisch, 2015;Weiss, Yakusheva, & Bobay, 2011). Eight studies (Cho, Kim, Yeon, You, & Lee, 2015;Dabney & Kalisch, 2015;Friese, Kalisch, & Lee, 2013;Kalisch, Tschannen, & Lee, 2011;Kalisch, Tschannen, Lee, & Friese, 2011;Kalisch et al, 2013;Orique et al, 2015;Palese et al, 2015) reported using a version of the MISSCARE survey (Kalisch & Williams, 2009); seven studies (Al-Kandari & Thomas, 2009;Ausserhofer, et al, 2014;Ball, et al, 2016;Ball, et al, 2014;Bruyneel, et al, 2015;Griffiths, Dall'Ora, et al, 2014;Zander et al, 2014) used a survey developed for the Registered Nurse Forecasting (RN4Cast) study (Sermeus et al, 2011).…”
Section: Included Studiesmentioning
confidence: 99%
“…Former studies in the USA indicate a variance in reports of MNC and its reasons by staff with different roles. With the exception of one study in the USA, RNs reported more MNC than did assistive personnel and nurse leaders reported more MNC than nursing staff . In a previous Icelandic study, role was identified as a contributing factor to missed nursing care supporting exploration of how nursing staff with different roles view omitted care .…”
Section: Introductionmentioning
confidence: 93%
“…Studies from a number of countries have revealed the patient and staff outcomes of missed nursing care . Inadequate labour and material resources are ranked the most common reasons for missed nursing care followed by communication . Previous studies have identified relationships of missed nursing care and patient outcomes such as falls, nosocomial infections, mouth care and patient satisfaction, as well as staff outcomes such as job satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…To establish workplace cultures that foster open dialogue regarding advocacy and patient safety concerns, it is recommended that nursing leadership consider the following interventional measures: Embed safer practices and mindfulness into existing structures and practices through policy enforcement (The Joint Commission, ) “Establish an organizational baseline measure on safety culture performance using the Agency for Healthcare Research and Quality (AHRQ) Hospital Survey on Patient Safety Culture (HSOPS) or another tool, such as the Safety Attitudes Questionnaire (SAQ) ” (The Joint Commission, , p. 4) Integrate safety culture training into quality improvement projects and strategic plans (Echevarria & Thorman, ; The Joint Commission, ) Provide a transparent dissemination of favourable and unfavourable care outcomes in order to promote accountability, ownership and pride of performance when advocacy and patient safety measures are evident (Echevarria & Thorman, ), and that distinguish between inadvertent human error, reckless actions and errors that are induced from poorly designed system approaches (The Joint Commission, ) Examine what elements of nursing care are often missed in acute and post‐acute settings in order to improve patient outcomes (Orique, Patty, & Woods, ) Leaders should model professionalism, respect and provide blame‐free communication opportunities that empower staff to speak out without fear of retaliation or confidential breaches, and provide opportunities for staff to learn from adverse events, close calls and unsafe practices (AHRQ, ; Hall et al, ; The Joint Commission, ; Vrbnjak et al, ) Solicit interdisciplinary and hierarchal input that seeks out solutions to address patient safety issues (AHRQ, ) Create/refine data reporting systems that capture near misses in order to determine resolutions that improve outcomes (Thoroman et al, ) Development of evidence‐based quality indicators to detect and review adverse events (Sabol & Caughey, ) …”
Section: Conclusion and Implications For Nursing Administrationmentioning
confidence: 99%